Breast pathology. Issue 1 (January 2016) - Bateman, Adrian C.; Shaw, Emily C.
Abstract: Cellular pathology is a key component of the breast disease multidisciplinary team (MDT), representing the 'gold standard' in the diagnosis of breast cancer and providing crucial information for determination of prognosis and management. Material may be obtained for pathological examination using fine needle aspiration (FNA) cytology, needle core biopsy or surgical excision (histopathology). Common benign conditions include fibrocystic change, fibroadenomas, intraduct papillomas and radial scars. Carcinoma is by far the most common malignant tumour and may exist as in situ or invasive forms. The use of mammography in the NHS Breast Screening Programme (NHS BSP) has resulted in the detection of breast cancers at an earlier stage of development (e.g. in situ carcinoma and small, low-grade invasive carcinomas). A recent comprehensive independent review has acknowledged the risk of over-diagnosis, whilst supporting the continuation of the programme due to evidence of overall benefit in terms of a reduction in breast cancer mortality. A cellular pathology report for a malignant breast excision specimen should include comments on the factors most pertinent to prognosis and management, such as tumour type, size, grade, and presence of vascular invasion and lymph node metastases. Assessment of the proximity of the tumour to the surgical margins will inform decisions regarding further surgical excision and radiotherapy, while identification of lymph node metastases will prompt consideration for chemotherapy in suitable patients. Cellular pathology techniques can also be used in predicting the likelihood of tumour response to hormonal manipulation and newer treatments such as trastuzumab. The application of increasingly sophisticated genomic technologies to breast cancer has enhanced the classification of the disease whilst highlighting new levels of complexity, and may lead to an improvement in both prognostication as well as the ability to better identify patients who may particularly benefit from chemotherapy and novel molecularly targeted therapies.